2021
DOI: 10.1371/journal.pgen.1009606
|View full text |Cite
|
Sign up to set email alerts
|

Permethrin resistance in Aedes aegypti: Genomic variants that confer knockdown resistance, recovery, and death

Abstract: Pyrethroids are one of the few classes of insecticides available to control Aedes aegypti, the major vector of dengue, chikungunya, and Zika viruses. Unfortunately, evolving mechanisms of pyrethroid resistance in mosquito populations threaten our ability to control disease outbreaks. Two common pyrethroid resistance mechanisms occur in Ae. aegypti: 1) knockdown resistance, which involves amino acid substitutions at the pyrethroid target site—the voltage-gated sodium channel (VGSC)—and 2) enhanced metabolism by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 50 publications
1
21
0
Order By: Relevance
“…aegypti may play an essential role in enhancing pyrethroid resistance, especially AAEL011338 in our populations. Still, other ankyrin genes may also be involved as indicated by the resistant mosquitoes from Mexico exhibiting enrichment for different ankyrin genes ( Campbell et al, 2019 ; Saavedra-Rodriguez et al, 2021 ). Since ankyrin is essential in microtubule dynamics ( Zhu et al, 2020 ) and synaptic stability ( Koch et al, 2008 ) in Drosophila , they could also be more directly implicated in resistance levels via structural changes in the synapse stability and neural activities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…aegypti may play an essential role in enhancing pyrethroid resistance, especially AAEL011338 in our populations. Still, other ankyrin genes may also be involved as indicated by the resistant mosquitoes from Mexico exhibiting enrichment for different ankyrin genes ( Campbell et al, 2019 ; Saavedra-Rodriguez et al, 2021 ). Since ankyrin is essential in microtubule dynamics ( Zhu et al, 2020 ) and synaptic stability ( Koch et al, 2008 ) in Drosophila , they could also be more directly implicated in resistance levels via structural changes in the synapse stability and neural activities.…”
Section: Discussionmentioning
confidence: 99%
“…There are several genes in this genome region, most with unknown functions. Other studies also pointed to several candidate genes involved in metabolic resistance or structural changes in the cuticle that could be correlated with increased resistance levels ( Campbell et al, 2019 ; Vera-Maloof et al, 2020 ; Saavedra-Rodriguez et al, 2021 ). All these genes may have an additive or synergistic effect with the kdr alleles on the overall resistance of a specific population, and studies relying only on one population may arrive at a large list of genes that may not be directly linked to pyrethroid resistance but rather reflect local adaptation or temporal variations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These types of mutations are often deleterious ( Saavedra-Rodriguez et al, 2021 ). In this study, SNP7 was identified as a non-synonymous mutation significantly associated with CaC at 9 months of age.…”
Section: Discussionmentioning
confidence: 99%
“…PC protein, an important component of the periphagous membrane of insect intestines, is mosquito’s first natural barrier against the invasion of foreign microorganisms. Recent studies have shown the importance of reducing the penetration of insecticides into the stratum corneum as a mechanism of mosquito resistance ( Saavedra-Rodriguez and Campbell, 2021 ). For example, thickening of the cuticle was associated with reduced permeability to pyrethroids in resistant mosquitoes in Anopheles gambiae ( Yahouédo et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%